2016
DOI: 10.24953/turkjped.2016.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Familial Mediterranean fever associated with optic neuritis, successfully treated with anti-interleukin 1 agents

Abstract: Here we described a boy who has been followed-up for FMF and attended with a loss of vision during the course of the disease. He was diagnosed with optic neuritis. As the other etiologies were excluded his optic neuritis was attributed to the underlying auto inflammatory process. After pulse steroid therapy, his symptoms improved and a complete remission occurred. Afterwards he had two more optic neuritis attacks. Thereafter anti-interleukin 1 (IL-1) drugs were introduced and he did not develop further attacks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Data on previous immunosuppressive therapy were available for 100 patients. [13][14][15][16][17][18][19][20][21] Forty-four patients used Anakinra prior to initiation of Canakinumab therapy. Of them, 26 had an intolerance to Anakinra and in 16 patients Anakinra was ineffective in preventing attacks.…”
Section: Indications For Canakinumabmentioning
confidence: 99%
See 1 more Smart Citation
“…Data on previous immunosuppressive therapy were available for 100 patients. [13][14][15][16][17][18][19][20][21] Forty-four patients used Anakinra prior to initiation of Canakinumab therapy. Of them, 26 had an intolerance to Anakinra and in 16 patients Anakinra was ineffective in preventing attacks.…”
Section: Indications For Canakinumabmentioning
confidence: 99%
“…The most common dose of Canakinumab was 2mg/kg in patients <40kg, or 150mg in those above. 13,17,18,[20][21][22][23][24][25][26][27][28] In case of inadequate disease control, an increase in dose to 3-4mg/kg in those below 40kg or 300mg in those over was used in 8 studies. 10,14,15,19,23,[29][30][31] In 8 studies, 10,19,22,[25][26][27][28]31 Canakinumab was given at 4-weekly intervals, in 3 studies 18,21,24 it was given at 8-weekly intervals, whereas the remaining studies had dosing frequencies tailored to clinical needs and/or protocols, with the medication being given every 4, 6 or 8 weeks.…”
Section: Dosing Of Canakinumabmentioning
confidence: 99%
“…MEFV gene encodes the protein pyrin. The gain of function mu-tations in the gene leads to activation of pyrin inflammasome and overproduction of interleukin-1, causing inflammation [4]. FMF is most commonly seen in the countries of the Mediterranean basin and the highest prevalence is observed in Turks, Armenians, Sephardic Jews and Arabs [1].…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been reported that uveitis, retinal ischemia, cataract, glaucoma and retinal detachment are related to FMF, optic nerve involvement has been rarely reported in the literature. 5 Alim et al evaluated the thickness of the peripapillary retinal nerve fiber layer (RNFL) and retinal ganglion cell-inner plexiform layer (GCIPL) in 42 adult-onset FMF patients by OCT but no relation was detected. 6 The inflammatory process mediated by IL-1β can be responsible for FMF-related optic nerve involvement.…”
Section: Discussionmentioning
confidence: 99%
“…6 The inflammatory process mediated by IL-1β can be responsible for FMF-related optic nerve involvement. 5 The diagnosis of case 1 was established as OPN related to adult-onset FMF. To the best of our knowledge this is the first case of OPN in medical literature associated with FMF.…”
Section: Discussionmentioning
confidence: 99%